Single nucleotide polymorphism in the rpoB gene Mycobacterium tuberculosis from Papua-Indonesia and its impact on rifampicin resistance: A whole genome sequencing analysis - Yustinus Maladan; Tri Wahyuni; Hana Krismawati (Microbiology Indonesia, 2021)
In the antibiotic era, Tuberculosis (TB) drugs resistance especially Rifampicin (RIF) is highly reported around the world. Resistance of RIF is caused by the mutation of genes that associated with RIF receptor. The aims of this study are detecting the Single Nucleotide Polymorphism of Rifampicin resistant genes using Whole Genome Sequencing (WGS) and analysing the profile of protein changing caused by SNP. Twenty Mycobacterium tuberculosis culture samples were passed on WGS procedure and 19 samples were adequate to further bioinformatics analysis. Single Nucleotide Polymorphisms Analysis was done using TBprofiler. Based on TBProfiler, seventeen samples were resistant to rifampicin. The mutations that cause the resistance are S450L, D435Y, H445Y, 430P, Q432K. Other Single Nucleotide Polymorphisms H835R, V534M and R224C were also found. The H835R mutants are present together with the S450L, V534M with S450L mutants, and R224C with Q432K mutants. Native protein for RNA Polymerase Subunit Î² used was the result of separation from the crystal structure of Mycobacterium tuberculosis H37Rv RNA polymerase (PDB: 5UHB). Binding affinity RIF to RNA Polymerase Subunit Î² calculated using AutoDock vina. Construction of mutant 3D structures using FoldX5. From the analysis, it was found that seventeen samples were resistant to rifampicin and two samples did not contain SNP which could cause resistance to rifampicin.